An Agent-Based Simulation Study of Guilt, Volunteering, and Social Norm Enforcement - Anjum, Muhammad Junaid; Fikri, Yahya; Tariq, Fatima (Robotics and Artificial Intelligence Review, 2025)
The present study uses Agent-Based Modeling (ABM) to study the intricate dynamics among diffusion of responsibility, subjective feeling of guilt, and their interaction impact on volunteering behavior when a context of norm violation exists. The process of responsibility diffusion is what classical studies on the bystander effect as a volunteer suppressor focus on. Our model generalizes this process by adding guilt to the list of cognitive elements triggered by an agent's inaction when witnessing violation of a norm. The simulation shows that even though observing bystanders who do not assist (diffusion of responsibility) initially suppresses volunteering, internalization and subsequent diffusion of guilt significantly lowers the threshold of reacting to non-volunteering agents in future encounters. Furthermore, the model demonstrates a causal link between spontaneous, efficient volunteering and an empirically measurable reduction in the convict's behavioral tendency to engage in further acts of norm violations. These emergent, macroscopic tendencies validate the theoretical prediction that guilt is an internal constraint capable of surmounting social inertia and hence acting as the main facilitator for self-organized social norm policing and collective deterrence in a population.